Pengaruh Konten Digital dengan Komunikasi Dialogis dan Narasi pada Emosi Krisis Negatif - Mentari Anugrah Imsa; Asep Soegiarto; Menati Fajar Rizki (Jurnal Riset Komunikasi (JURKOM), 2024)
Abstract The current technological development is progressing rapidly, accompanied by advancements in communication processes, where the exchange of information occurs very easily, especially on social media. The existing social media platforms nowadays enable users to express opinions, experiences, and various other information, known as User-generated content (UGC). UGC related to company information could not be controlled by the company, even during the crisis. Therefore, this research aims to measure the influence of the types of content created by the public (dialogic content and narrative content) on the negative crisis emotions experienced by other members of the public. This research follows a positivist paradigm with a quantitative approach, conducting an experiment. The study assesses the changes in negative crisis emotions among the public regarding the crisis of the Sanmol syrup medication. The research sample consists of 118 respondents selected by purposive sampling techniques. The results of the study indicate that there is no significant change in negative crisis emotions after exposure to dialogic and narrative content treatments. Keywords: crisis, digital content, dialogis communication, narrative, negative crisis emotion